Pharmacophore Analysis and Phytochemical Studies of Rhodomyrtus tomentosa Leaves as Analgesic Agent - Mohammad Farhan Ariffeen, Rosli (Universiti Malaysia Sarawak (UNIMAS), 2019)
Rhodomyrtus tomentosa leaves was extracted and isolated using chromatography approach to give 3 compounds. EA-1, EA-2, and MeOH-1 were elucidated as tomentosin, 1,5-transguaianolides, and arjunolic methyl ester, respectively. Isolated and reported compounds were assigned as test set, and virtually evaluated using pharmacophore analysis approach. LigandScout 4.2 was utilized for analysis. Drugs for pain treatment were selected as training set for generation of model. The test set were aligned to the model generated, compounds with common features show good fit-value. Crystal structure of COX-2 was selected as target complex. The interactions of test set in the binding site were observed. In vitro and in vivo assay were conducted to observe the analgesic effect of extracts and isolated compounds. As a results, EA-2 showed high fit value with 35.73, followed by MeOH-1 (34.22) and EA-1 (31.03). Rhodomyrtosone G, rhodomyrtosone B, rhodomytone and piceatannol-4-O-β-D-glucoside also showed good fit value. EA-2, MeOH-1 and rhodomyrtosone G showed high alignment score to binding site of COX-2 complex with 45.55, 55.88, and 65.57, respectively. EA-2 and rhodomyrtosone G were associated to active orally drugs. MeOH fraction extract showed potent DPPH scavenging activity, with EC50 value of 144.2 mg/mL. In acute toxicity test, the LD50 of the extracts were estimated to be more than 2000 mg/kg. EA-2 and MeOH-1 showed significant analgesic effect on treated mice at the early phase. It was concluded that EA-2 and MeOH-1 possessed analgesic properties, and further investigation could be performed to study structure activity relationship of the compounds.